2020
DOI: 10.1002/nav.21900
|View full text |Cite
|
Sign up to set email alerts
|

On the computational complexity of the patrol boat scheduling problem with complete coverage

Abstract: Our study is primarily concerned with analyzing the computational complexity of the patrol boat scheduling problem with complete coverage (PBSPCC). This combinatorial optimization problem has important implications for maritime border protection and surveillance operations. The objective of the PBSPCC is to find a minimum size patrol boat fleet to provide ongoing continuous coverage at a set of maritime patrol regions, ensuring that there is at least one vessel on station in each patrol region at any given tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Applications for the PSRP can be widely found in different areas. Regarding the scheduling and routing problem for the security personnel, rounds of visits are conducted to various customer premises over a 24 h period in different locations, often using vehicles to travel between locations and then walking within the facilities [24][25][26]. In the healthcare domain, the home care problem entails local authorities offering community care services to residents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Applications for the PSRP can be widely found in different areas. Regarding the scheduling and routing problem for the security personnel, rounds of visits are conducted to various customer premises over a 24 h period in different locations, often using vehicles to travel between locations and then walking within the facilities [24][25][26]. In the healthcare domain, the home care problem entails local authorities offering community care services to residents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are static, dynamic solutions for boundary surveillance. Dynamic solutions include different patrol mechanisms [ 25 , 26 ]. Generally, short—a few hours—flight times are typical for drones [ 27 ], but developments aiming at flight times of several hours [ 28 ] also exist.…”
Section: Related Literaturementioning
confidence: 99%
“…Surendonk and Chircop 2 have recently shown that the PBSPCC belongs firmly within the non-deterministic polynomial-time (NP)-hard computational complexity class. In contrast, related problems in the literature, such as the Maximum Covering and Patrol Routing Problem (MCPRP), 3,4 have been shown to exhibit only polynomial-time worst case complexity.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the NP-hard classification established by Surendonk and Chircop. 2 It has been observed that when using an objective function that seeks to minimize the total number of vessels, the column generation procedure is slow to produce good quality candidate patrol boat schedules. In order to speed-up the solution time, this paper proves a number of conditions under which an alternative objective, namely, minimize the total non-patrol time , can be used to arrive at a solution of the original problem.…”
Section: Introductionmentioning
confidence: 99%